Life Science Research Immersion Program Improves STEM-Specific Skills and Science Attitudes among Precollege Students - Maysoon Lehmeidi Dong; Zuying Feng; Flannery McLamb; Lindsey Griffin; Armando Vazquez; Ken K. Hirata; Liisa Bozinovic; Miguel F. Vasquez; Goran Bozinovic (Journal of Microbiology & Biology Education, 2023)
ABSTRACT A predicted rapid growth in science, technology, engineering, and math (STEM) careers demands a vast and talented workforce, but students most commonly abandon STEM majors within the first 2 years of college. Performance in introductory courses, scientific literacy, and the ability to critically reason are main predictors of retention in STEM, highlighting the importance of precollege and early college experience. The Life Science Research Immersion Program (LSRIP) is a novel science education model that focuses on the development of scientific research skills, thus preparing students for introductory college courses and beyond. To evaluate the efficacy of the LSRIP, pre- and postprogram assessments and surveys were administered to three precollege student cohorts. Scientific reasoning assessment scores improved by 4.70% in Summer 2019 (P < 0.01), 9.44% in Fall 2019 (P < 0.05), and 0.97% in Winter 2020 cohorts, with two of five questions showing statistically significant improvement. Surveyed attitudes toward science improved in 62.9% of questions across all cohorts. These results suggest that research immersion experiences are an effective educational instrument for improving and promoting scientific reasoning and attitudes among precollege students. To better prepare students for success in STEM higher education and careers, we recommend implementing LSRIPs to complement traditional precollege science curricula.